Algoritma Penjadwalan Job Shop Alternatif Routing Menggunakan Variable Neighborhood Descent With Fixed Threshold Untuk Minimisasi Makespan - HARTINI, SEPTIANI; Zaini, Emsosfi; Imran, Arif (REKA INTEGRA, 2013)
Makalah ini membahas algoritma penjadwalan job shop alternatif routing menggunakan variable neighborhood descent (VND) with fixed threshold dengan kriteria minimisasi makespan. Tahap-tahap yang dilakukan pada algoritma ini yaitu tahap konstruksi dan tahap local search. Pada tahap konstruksi, urutan jadwal awal dibuat menggunakan penjadwalan non delay yang telah dimodifikasi. Pada tahap local search perbaikan urutan jadwal menggunakan proses insert dan exchange terhadap struktur neighborhood secara deterministik. Data-data hipotetik yang digunakan pada makalah ini merupakan data-data dari literatur. Â  Kata kunci: Job shop, alternatif routing, variable neighborhood descent with fixed threshold Â  ABSTRACT This paper discusses the scheduling algorithm of job shop with alternative routing using variable neighborhood descent (VND) with a fixed threshold for the makespan minimization criteria. The stages are performed on this algorithm, namely the construction phase and stage of local search. On the construction phase the sequence of initial schedules created using the non delay scheduling that has been modified. At this stage of local search repair sequence schedule by using the insert and exchange process of deterministic structure in neighborhood. Hipotetik Data used in this paper is the data from the literature. Keywords: Job shop, alternative routing, variable neighborhood descent with fixed threshold